Integrated planning and scheduling built on cluster analysis and simulation optimisation. (1st January 2014) - Merkuryeva, Galina; Bolshakov, Vitaly
This paper proposes integrated solutions for product delivery planning and scheduling in distribution centres. Cluster analysis, computer simulation and metaheuristic optimisation are applied to improve planning decisions at tactical and operational levels. An integrated approach to product delivery planning and scheduling built on integration of these technologies is described. A cluster analysis of product demand data of stores is used to identify typical dynamic demand patterns and associated product delivery tactical plans. Customer regional clusters are built through multi-objective optimisation. Metaheuristic optimisation techniques are applied to define optimal parameters of product transportation and delivery schedules. Here, vehicle scheduling is performed for the routed solution. Integrated solutions are illustrated and adjusted to a specific business case.